Moldova Trade Study : Note 4. The Performance of Free Economic Zones in Moldova - World Bank (Washington, DC, 2016)
In 1995, Moldova introduced free economic zone (FEZ) legislation with the aim of accelerating socioeconomic development by attracting domestic and foreign investment, promoting exports, and creating employment. Since then, seven free economic zones offering tax and customs benefits have been established. This note assesses the static and dynamic economic benefits of the program in Moldova. The free economic zones have been successful in attracting investment from both domestic and foreign sources. The economic zones have become true export platforms, generating a five-fold increase in exported industrial production from the zones between 2004 and 2014. On average, employment in the economic zones had a robust growth in the last seven years and almost doubled since 2008. Evidence suggests that the economic zones have significantly contributed to the diversification of exports and to the changing structure of the Moldovan economy. The effect of the economic zones on domestic firms appears to be modest, however, and unlikely to contribute to the technological upgrading and sophistication of the Moldovan economy. Free economic zones tend to attract industrial activities requiring intensive use of human resources for certain operations. The economic impact of Moldovan free economic zones is ambiguous. Moldovan legislation provides sound and transparent provisions, but the main issue is how this legislation is implemented. The majority of recommendations are focused on streamlining the implementation process, making it easier for companies to operate. Here are the main recommendations for improving the zones : (i) the importance of fiscal incentives should be downgraded by shifting to targeted services for businesses; (ii) reduce corruption and increase accountability by establishing one-stop-shop procedures and elements; (iii) establish a proper mechanism for monitoring and reporting with the zones residents and administrator; (iv) empower the regulator with additional relevant institutional capacities and capabilities; (v) the role of residents in appointing the administrator should be determinant; and (vi) establish a proper mechanism for compensating residents of the zones for restrictive treatment of the real assets.